Miscellaneous photographs from Hummel collection (2023)
Four photographs from the Hummel collection, including: a) interior of unidentified building in Buchara, Turkestan, dated 1896 on verso; b) unidentified photographs of men and horses in ? Turkestan, dated 1893 on verso; c) program from a concert in Pressburg on 3 April 1881 for the "Hummel-Denkmal_Fondes" with Géza Zichy, Aladár Juhász, and Franz Liszt; d) announcement of a performance by J. N. Hummel when he was 15 years old, dated 15 March 1795.